2020
DOI: 10.1002/cam4.3356
|View full text |Cite|
|
Sign up to set email alerts
|

Tetrandrine sensitizes nasopharyngeal carcinoma cells to irradiation by inducing autophagy and inhibiting MEK/ERK pathway

Abstract: Nasopharyngeal carcinoma is one of the common malignant tumors in South China. The age-standardized incidence rate of nasopharyngeal carcinoma in southern China has reached 20 per 100 000, while that is more than 1 per 100 000 person in most areas of the world. 1 Radiotherapy is the most important treatment modality for nasopharyngeal carcinoma due to the complicated anatomical structure and undifferentiated non-keratinizing type as the main pathological type. 2 While the 5-year overall survival rate can be as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Downregulation of ERK phosphorylation can promote G2/M phase arrest of human leukemia cells through ERK inhibitors 34 . Tetrandrine increased the radiosensitivity of NPC cells (CNE‐1 and CNE‐2) by inhibiting ERK phosphorylation under the maximum non‐cytotoxic dose condition but has shown no correlation to the p38 and JNK pathways 18 . In particular, inhibition of the MEK/ERK/c‐MYC pathway inhibits the cell proliferation, migration, and invasion of NPC 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Downregulation of ERK phosphorylation can promote G2/M phase arrest of human leukemia cells through ERK inhibitors 34 . Tetrandrine increased the radiosensitivity of NPC cells (CNE‐1 and CNE‐2) by inhibiting ERK phosphorylation under the maximum non‐cytotoxic dose condition but has shown no correlation to the p38 and JNK pathways 18 . In particular, inhibition of the MEK/ERK/c‐MYC pathway inhibits the cell proliferation, migration, and invasion of NPC 18 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in several preclinical models, RAS–RAF–MEK–ERK pathway inhibitors and CDK4/6 inhibitors exerted better tumor suppressor effects when used in combination 17 . In particular, inhibition of the MEK/ERK/c‐MYC pathway can downregulate cell proliferation, migration, and invasion of NPC 18 . Previous studies have shown that lapatinib mediates an increase in the radiosensitivity of breast cancer by inhibiting the Raf/MEK/ERK mitogen‐activated protein kinase cascade reaction 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Tetrandrine (TET) possesses multiple pharmacological properties against a wide variety of cancers [ 163 ]. The antitumor effects of TET are associated with the induction of apoptosis and autophagy, the reversal of MDR, and the enhancement of radiation sensitization [ 163 , 164 ]. TET has been proven to be a potent broad-spectrum autophagy agonist with effects on a variety of cell lines, including triple-negative breast cancer cells, human HCC, nasopharyngeal carcinoma by inhibiting PI3K/AKT/mTOR signaling [ 164 , 165 ].…”
Section: Natural Products As Inducers Of Autophagy In Cancermentioning
confidence: 99%
“…The antitumor effects of TET are associated with the induction of apoptosis and autophagy, the reversal of MDR, and the enhancement of radiation sensitization [ 163 , 164 ]. TET has been proven to be a potent broad-spectrum autophagy agonist with effects on a variety of cell lines, including triple-negative breast cancer cells, human HCC, nasopharyngeal carcinoma by inhibiting PI3K/AKT/mTOR signaling [ 164 , 165 ]. TET inhibits human PML-RARα-positive acute promyelocytic leukemia (APL) cell proliferation and induces autophagy by activating ROS generation and Notch1 signaling [ 261 ].…”
Section: Natural Products As Inducers Of Autophagy In Cancermentioning
confidence: 99%
“…In the article by Wang et al, 1 the authors would like to add two additional funding sources under funding information:…”
mentioning
confidence: 99%